Graphical User Interface for educational content programming with social robots activities and how teachers may perceive it - Tozadore, Daniel Carnieto; Romero, Roseli Aparecida Francelin (Revista Brasileira de Informática na Educação, 2020)
<span data-sheets-value=""1":2,"2":"Interactive devices have been successfully applied in education in the last decades. The most used devices for such tasks are personal computers and tablets, due to its financial trade-off and popularization. Social robots are less used, mainly because of its cost and the complexity of being programmed. In this paper, a solution to work around the complexity of programming social robots is presented as a Graphical User Interface (GUI). The GUI system controls an interactive robot which plays with the students and adapts its behavior autonomously. During the activity execution, the adaptive algorithm detects student’s body signals and verbal responses to adapt the addressed content to harder or easier questions. After creating and running an activity, all sessions’ evaluation and information can be accessed for visual analysis, as well as students’ preferences throughout the interaction. The proposal was presented to regular teachers from the elementary school that answered a questionnaire about their perception about the proposal. The answers were analyzed and, in general, they seemed to slightly notice the system potential in and how it can support them in after-classes exercises, despite it require some time to fully get used with the interface."" data-sheets-userformat=""2":513,"3":"1":0,"12":0">Interactive devices have been successfully applied in education in the last decades. The most used devices for such tasks are personal computers and tablets, due to its financial trade-off and popularization. Social robots are less used, mainly because of its cost and the complexity of being programmed. In this paper, a solution to work around the complexity of programming social robots is presented as a Graphical User Interface (GUI). The GUI system controls an interactive robot which plays with the students and adapts its behavior autonomously. During the activity execution, the adaptive algorithm detects student’s body signals and verbal responses to adapt the addressed content to harder or easier questions. After creating and running an activity, all sessions’ evaluation and information can be accessed for visual analysis, as well as students’ preferences throughout the interaction. The proposal was presented to regular teachers from the elementary school that answered a questionnaire about their perception about the proposal. The answers were analyzed and, in general, they seemed to slightly notice the system potential in and how it can support them in after-classes exercises, despite it require some time to fully get used with the interface.